Plato's Laws : Force and Truth in Politics - Sanday, Eric; Recco, Gregory (Book collections on Project MUSE., 2012)
"Readers of Plato have often neglected the Laws because of its length and density. In this set of interpretive essays, notable scholars of the Laws from the fields of classics, history, philosophy, and political science offer a collective close reading of the dialogue "book by book" and reflect on the work as a whole. In their introduction, editors Gregory Recco and Eric Sanday explore the connections among the essays and the dramatic and productive exchanges between the contributors. This volume fills a major gap in studies on Plato's dialogues by addressing the cultural and historical context of the Laws and highlighting their importance to contemporary scholarship."--Provided by publisher.